The politics of reform and the making of the second reform act, 1848-1867 - Saunders, R (2007)
The second reform act came at the close of a remarkable period of constitutional debate, in which seven different governments had committed themselves to reform. Yet historians have shown little interest in this debate, seeing it as largely irrelevant to the making of the second reform act. This article seeks to reconnect the discussions of the 1850s with the measure of 1867, and to explore some of the issues that shaped the course of legislation. It argues that the failure to achieve reform in the 1850s was the result not of hostility to reform in the abstract, but of an inability to agree on the type of reform that was desirable. Depending on who was enfranchised and where, different reform bills could produce quite different electorates, making consensus elusive. The article shows how the Liberal opposition to the 1866 bill was fuelled by concerns over the nature of Liberal politics after Palmerston, and concludes that the disagreement over the rating franchise concealed a wider disagreement on the whole nature of reform, exerting a powerful influence on the measures of both 1866 and 1867. © 2007 Cambridge University Press.